2017
DOI: 10.1007/s00784-017-2111-5
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cephalometric investigation of two fixed functional orthodontic appliances in class II treatment: Functional Mandibular Advancer vs. Herbst appliance

Abstract: Treatment leads to overjet and molar relationship correction that is mainly caused by significant dentoalveolar changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Therefore, studies related to the effects of the device used in the methodology of the present study, showing the same effects on teeth 5,[17][18][19] , should be interpreted with caution, as there is a tendency to assume these changes lead to worse facial esthetic perception, which does not seem to fit the reality.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, studies related to the effects of the device used in the methodology of the present study, showing the same effects on teeth 5,[17][18][19] , should be interpreted with caution, as there is a tendency to assume these changes lead to worse facial esthetic perception, which does not seem to fit the reality.…”
Section: Discussionmentioning
confidence: 94%
“…However, even with the present sample, it was possible to verify that cephalometric measurements tend to behave similarly in all patients, following the behavior detected in studies previously published in the literature that focused on cephalometric changes resulting from treatment with mandibular protractors. Thus, variable behaviors were expected to be similar, without differences between the two groups studied 5,[17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, long-term side effects are more complex and involve skeletal and dental modifications. The mechanism behind these changes is the same as those described for orthodontic functional appliances: when the muscles are stretched by the device due to the forward posturing of the mandible, forces are transmitted to the bones and the teeth, and the long duration of these forces produces changes in skeletal morphology and teeth position 21 . The dental and skeletal changes are progressive, and thus patients should be monitored over time, and are also dependent on the duration of the MAD therapy 13 .…”
Section: Discussionmentioning
confidence: 95%
“…21,41,42 When comparing the results of the present study with other functional appliances evaluated in the same age period, it seems that treatment effects do not depend on the type of fixed functional appliance used. Kinzinger et al 6 found that most of the overjet and molar relationship correction were Class II Treatment Effects after the Growth Peak Cançado et al…”
Section: Intergroup Comparisonmentioning
confidence: 99%